Caveolae-Associated Protein (cavin)-4 Autoantibodies in Immune Mediated Rippling Muscle Disease. (5th December 2022) - Hammami, M Bakri; Beecher, Grayson; Knight, Andrew; Liewluck, Teerin; Triplett, James; Datta, Abhigyan; Dasari, Surendra; Zhang, Youwen; Roforth, Matthew; Jerde, Calvin; Murphy, Stephen; Litchy, William; et al.
Abstract : Objective: To describe a novel autoantibody biomarker of Immune mediated rippling muscle disease (iRMD). Background: iRMD is a rare immunotherapy-responsive myopathy characterized by wave-like muscle contractions (rippling) and percussion/stretch-induced muscle mounding. However, serological biomarker of this disease is lacking. Design/Methods: A Retrospective review was done to identify iRMD patients with stored sera in Mayo Neuroimmunology laboratory. Archived sera from IRMD patients were evaluated for a common biomarker of IRMD using phage immunoprecipitation sequencing (PhIP-Seq). Results: Archival sera from 10 patients with clinical diagnosis of iRMD were retrieved. Whole human proteome PhIP-Seq identified peptides corresponding to different regions of the cavin-4 in sera of iRMD patients. Eight of the ten iRMD cases were positive for cavin-4 IgG by immunofluorescent cell-based-assay (CBA) using cavin-4-transfected COS7 cells. The cavin-4-reactive IgG in all 8 positive sera was of IgG1 subclass. None of the disease control sera (98 immune-mediated myopathy/neuromuscular junction disorders, 20 autoimmune CNS diseases and 123 healthy subjects) contained cavin-4-reactive IgG. Furthermore, none of the iRMD patients' sera were positive for caveolin-3 IgG. The majority of seropositive cases were males (6/8, 75%) with median age of 51 years (range 18-76). Three seropositive patients had co-existing myasthenia gravis (38%). Creatine Kinase was elevated in 6/7 tested patients (median 771 U/L, range: 132-2625 U/L). Muscle biopsy was performed in 7 of the 8 cavin-4 IgG seropositive patients; 6/6 specimens analyzed immunohistochemically revealed a mosaic pattern of sarcolemmal cavin-4 immunoreactivity. Three of 6 seropositive patients who received immunotherapy had complete resolution of symptoms; one had mild improvement and two had no change. Conclusions: Cavin-4 IgG is a novel and specific serological autoantibody biomarker identified in iRMD. Depletion of cavin-4 expression in iRMD patient muscle biopsies suggests the potential role of this autoantigen in disease pathogenesis.